Periprotetické zlomeniny v oblasti kyčelního kloubu - Weissinger, Manfred; Helmreich, C; Pöll, G (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2009)
PURPOSE OF THE STUDY It is the aim of our study to present the results of our way of treatment of the periprosthetic fractures, with the cemented as well as the cement-free stems. MATERIAL From 1.1.1988 until 31.3.2005 we operated 42 periprosthetic fractures of the hip in 41 patients. 31 of our patients were females, 10 of them males. In 22 cases we operated the right side, 18 times the left side and once we had to operate both sides, but at different times. We used the Vancouver classification scale for the grading of the fractures. In our study we excluded type A fractures; we registered 41 type B fractures and one only type C fracture. The reason for periprosthetic fracture in all these 42 cases was definitely a trauma. In 6 cases we found pre-existing loosening of the stem. We have grouped our patients under two headings: 1. Primary cemented stems (n=13) 2. Primary cement-free stems (n=29) The average age at the time of primary operation was 63,6 years in the group of cemented stems and 67,2 years with the cement-free implants. METHODS The principle of this operation lies in a stable technique of osteosynthesis. If one operates on a stable stem one uses a one and only technique of osteosynthesis. Patients who also suffer from a loosening of the stem, are treated by replacement of the stem combined with a particular form of osteosynthesis. We generally use a transgluteal access with an L-shaped detachment of the Musc. vastus lateralis. In the group of cemented stems (n=13) we carried out a replacement of the stem 6 times and in the group of cement-free stems (n=29) we had to replace the implant on 7 occasions. Analysing the osteosynthesis technique we find the use of titanium cerclages and titanium elements on 35 occasions, in both groups taken together. As implant for the stem we preferred the modulated revision stem according to Zweymüller. Clinical post-operational examination of our patients was carried out according to the Merle d?Aubigne score and two x-rays at different levels. RESULTS After an average post-operational check-up time of 3 years and 2 months, we were able to examine 8 patients with cemented stems (61,5 %), 4 of whom had replacement of the stem by a cement-free implant. In the cement-free group we evaluated 24 patients after an average time of 4 years and 11 months. In this group we had 5x a replacement of the stem, 3x of these we could operate cement-free. The post-operational radiological check showed an excellent building-up of bone structure without any dislocation of the implant in all 32 cases. DISCUSSION The average age of our patients shows 77 years with those with cemented stems and 74,5 years in the ones with cement-free implants. Analysis of the cemented stems shows a loosening rate of more than 50 %, which coincides with the findings of many other authors. After a couple of years using cups of polyaethylene we were confronted with the problem of the so-called Polyaethylene disease. These alterations may finally lead to a loss of bone quality, to mechanical loosening of the implant and an increase in danger of fracture. When we discuss the group of patients with cement-free stems and compare them to those with cemented ones, we find a number of quite different characteristics. B2 fractures appear in a quite higher number of patients with cemented and loosened stems. In this regard, our own study is congruent with the studies of other authors. In the cement-free group we had 75 % B1 fractures with a stable stem. The explanation for these figures is, that the cement-free implants were well incorporated in the bone structure. CONCLUSIONS The choice of operative procedure when treating periprosthetic hip fractures depends on the type of fracture and the stability of the prosthesis. Our own very positive experiences and the then emerging results lead to a certain strategy in procedure. That means, for us, the use of a cement-free modulated revision stem according to Zweymüller combined with a particular technique of osteosynthesis, using titanium cerclages and titanium elements.
Keywords: Female; kyčelní protézy; fraktury kyčle; ženské pohlaví; lidé; Aged, 80 and over; cementování; Cementation; Male; Aged; náhrada kyčelního kloubu; vnitřní fixace fraktury; lidé středního věku; senioři nad 80 let; Arthroplasty, Replacement, Hip; senioři; mužské pohlaví; Middle Aged; Hip Prosthesis; Fracture Fixation, Internal; Hip Fractures; Humans